A hybrid color emotional experience approach: Integrating the pleasure-arousal-dominance model with fuzzy grey relational analysis - Tianyu Wu; Tianlu Zhu; Yiqian Zhao; Cengjuan Wu (PLoS ONE, 2026)
Color schemes are a crucial component of modern product design and user experience, closely linked to users’ emotional needs. However, emotional experiences with product colors are inherently complex and abstract. Accurately capturing these emotional tendencies and translating them into effective color schemes has long been a challenge in emotional design. This study proposes an emotional experience-based approach to product color matching, grounded in Kansei Engineering (KE). To establish a robust closed-loop between design and evaluation, both forward and reverse KE models were developed, accompanied by comprehensive evaluation methods ranging from color factor analysis to the optimization of final schemes. Given the vagueness and complexity of the experiential data obtained from 216 questionnaires, the Pleasure-Arousal-Dominance (PAD) model was integrated with fuzzy Grey Relational Analysis (GRA) to extract nuanced and meaningful insights. Using the color design of a household hair dryer as a case study, the feasibility of the framework was demonstrated. Comparative results showed that, the proposed PAD–fuzzy GRA approach produces more stable and discriminative evaluation outcomes for intermediate schemes. Moreover, the resulting rankings exhibited a higher degree of consistency with independent eye-tracking measurements, indicating a closer alignment with users’ actual visual attention and emotional perception. The proposed methodology effectively captures users’ emotional responses to specific color schemes without relying on overly complex calculations or experimental conditions. It aligns with subjective visual preferences and identifies color combinations that evoke positive emotions. By incorporating practical design psychology methods, this hybrid design and evaluation framework offers an intuitive and applicable reference for emotional experience, extending beyond conventional color matching.